The 1st International E-Conference on Antioxidants in Health and Disease 2020
DOI: 10.3390/cahd2020-08594
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic and Flavonoid Content and In Vitro Antioxidant Activity of Methanol Extract and Solvent Fractions of Desmodium ramosissimum G. Don

Abstract: Oxidative stress has been linked to the pathogenicity of many diseases. This study investigated the total phenolic content (TPC) and total flavonoid content (TFC) of the methanolic extract and solvent fractions (n-hexane, ethyl acetate, n-butanol, and aqueous) of Desmodium ramosissimum using Folin–Ciocalteu and aluminum chloride assays, respectively. The extract and solvent fractions were further appraised for their in vitro antioxidant capacity using total antioxidant capacity (TAC), 2, 2-diphenyl-1-picrylhyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…Hence, E.F showed a significantly higher antioxidant potency (p < 0.05) as analysed by molybdate ion reduction assay. This result is consistent with previous research on Desmodium triflorum(Lai et al, 2010) and Desmodium ramosissimumis(Ezealigo et al, 2021). As reported byLai et al (2010) andEzealigo et al (2021), the higher antioxidant activity expressed in the ethyl-acetate fraction of the Desmodium plant is due to the higher total phenolic content.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Hence, E.F showed a significantly higher antioxidant potency (p < 0.05) as analysed by molybdate ion reduction assay. This result is consistent with previous research on Desmodium triflorum(Lai et al, 2010) and Desmodium ramosissimumis(Ezealigo et al, 2021). As reported byLai et al (2010) andEzealigo et al (2021), the higher antioxidant activity expressed in the ethyl-acetate fraction of the Desmodium plant is due to the higher total phenolic content.…”
supporting
confidence: 93%
“…This result is consistent with previous research on Desmodium triflorum(Lai et al, 2010) and Desmodium ramosissimumis(Ezealigo et al, 2021). As reported byLai et al (2010) andEzealigo et al (2021), the higher antioxidant activity expressed in the ethyl-acetate fraction of the Desmodium plant is due to the higher total phenolic content. Similarly, in this study, E.F. presented with a higher total phenolic when compared with M.E and the fraction, B.F.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The authors concluded that DPPH-free radical scavenging activity of methanolic extracts of A. leiocarpus and M. oleifera was similar to vitamin C and was better expressed as compared with B. refescens, I. asarifolia, G. senegalensis ( 145 ). A similar antioxidative effect and DPPH-free radical scavenging activity was also reported for methanolic extract of Desmodium ramosissimum, which could be another rich source of natural antioxidants, justifying its pharmacological use in traditional medicine ( 178 ).…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...supporting
confidence: 64%
“…In D. sequax chlorogenic acid is the main component of the antioxidant activity (Tsai et al, 2011). Many of the studies suggest that the effect is evidenced in a concentration-dependent manner and that the antioxidant potential varies depending on the solvent used in the extraction because each extract possesses unique chemical constituents (Sankar et al, 2013;Li et al, 2014a;Ezealigo, 2016).…”
Section: Republic Of the Congomentioning
confidence: 99%